1990
DOI: 10.1161/01.cir.81.2.506
|View full text |Cite
|
Sign up to set email alerts
|

Mildly dilated congestive cardiomyopathy. Use of prospective diagnostic criteria and description of the clinical course without heart transplantation.

Abstract: Prognosis in classically described dilated congestive cardiomyopathy has been reported to be related to ventricular size. Mildly dilated congestive cardiomyopathy (MDCM) has been defined as end-stage heart failure of unknown etiology (New York Heart Association class IV, left ventricular ejection fraction less than 30%), occurring with neither typical hemodynamic signs of restrictive myopathy nor significant ventricular dilatation (less than 15% above normal range). The present study includes follow-up in 12 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Previously reported echocardiographic manifestations of fulminant myocarditis include global and regional systolic and diastolic dysfunction 2,5,6,10-12,14 and lack of LV dilatation. 2,5,6,13,14 Felker et al reported that 14 patients with fulminant myocarditis presented with non-dilated, thickened, hypocontractile ventricles in the acute phase, but showed significant improvement in LV contraction 6 months after discharge, 14 and their findings are generally consistent with ours, although none of their patients was treated with PCPS.…”
Section: Discussionsupporting
confidence: 82%
“…Previously reported echocardiographic manifestations of fulminant myocarditis include global and regional systolic and diastolic dysfunction 2,5,6,10-12,14 and lack of LV dilatation. 2,5,6,13,14 Felker et al reported that 14 patients with fulminant myocarditis presented with non-dilated, thickened, hypocontractile ventricles in the acute phase, but showed significant improvement in LV contraction 6 months after discharge, 14 and their findings are generally consistent with ours, although none of their patients was treated with PCPS.…”
Section: Discussionsupporting
confidence: 82%
“…Some investigators have found histological changes that appear to be related to left ventricular haemodynamics and prognosis,12 while others have failed to show such a correlation 213 14 Nevertheless, in recent years specimens obtained at endomyocardial biopsy have proved useful in exploring the cellular and molecular abnormalities of the failing human myocardium in vivo 1516 …”
mentioning
confidence: 99%
“…12,19) On the other hand, several investigators have reported that the prognosis of DCM patients with mild LV dilatation is variable and that end-stage heart failure occurs in a subgroup of patients with DCM despite mild LV dilatation. [20][21][22][23] We previously reported that DCM patients with mild LV dilatation have two important features: one group of patients with early and mild DCM may stabilize or improve through the natural course or with appropriate medi- 71.0 ± 20.6 (n = 5) 64.5 ± 20.6 (n = 15) 0.546 E/Ea septal 12.0 ± 3.3 (n = 2) 15.9 ± 7.0 (n = 7) 0.479 Laboratory data BNP, pg/mL 700.1 ± 532.5 (n = 3) 328.5 ± 307.1 (n = 10) 0.144 Creatinine, mg/dL 1.03 ± 0.49 (n = 3) 0.93 ± 0.16 (n = 10) 0.753 Sodium, mmol/L 140.7 ± 3.2 (n = 3) 139.9 ± 2.5 (n = 11) 0.667 Total bilirubin, mg/dL 1.30 ± 1.13 (n = 2) 0.72 ± 0.22 (n = 11) 0.599…”
Section: Discussionmentioning
confidence: 99%